2016
DOI: 10.1111/jeb.13018
|View full text |Cite
|
Sign up to set email alerts
|

Local adaptation of reproductive performance during thermal stress

Abstract: Considerable evidence exists for local adaptation of critical thermal limits in ectotherms following adult temperature stress, but fewer studies have tested for local adaptation of sublethal heat stress effects across life-history stages. In organisms with complex life cycles, such as holometabolous insects, heat stress during juvenile stages may severely impact gametogenesis, having downstream consequences on reproductive performance that may be mediated by local adaptation, although this is rarely studied. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(112 citation statements)
references
References 55 publications
3
108
1
Order By: Relevance
“…Latitudinal clines in responses to thermal stress have been observed in D. subobscura (Porcelli et al ., ). However, there is little evidence for local adaptation in male thermal stress across shorter distances, even when – as in this case – thermal regimes vary at similar magnitudes locally to those observed across a given species' latitudinal range.…”
Section: Discussionmentioning
confidence: 99%
“…Latitudinal clines in responses to thermal stress have been observed in D. subobscura (Porcelli et al ., ). However, there is little evidence for local adaptation in male thermal stress across shorter distances, even when – as in this case – thermal regimes vary at similar magnitudes locally to those observed across a given species' latitudinal range.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how species respond to climate change is a pertinent theoretical question and an immediate conservation priority (Hoffmann & Sgrò 2011;Kellermann et al, 2009;Porcelli, Gaston, Butlin, & Snook, 2017). A recent study of two Hawaii Island endemic picture-winged Drosophila, the rare D. silvestris and the more ubiquitous D. sproati, found strong species-level differences in temperature tolerance (Uy et al, 2015), and previously observed clinal patterns of genetic differentiation in D. silvestris (Craddock & Carson 1989) suggest that temperature may also be driving adaptive population divergence.…”
mentioning
confidence: 99%
“…Honey bee queens (Kona Queens supplied in a single shipment) were treated at one of five different temperatures (5,10,15,25,38,40, and 42 ͦ C) for 1, 2, or 4 hours, then held at 25 ͦ C for 2 d. Fourteen queens (replicates) were included in the 25 ͦ C treatment (negative control), whereas 8-9 queens were included in all other temperatures and exposure durations (see Table 1 for replication information). Following this, queens were beheaded, and their spermathecae were dissected with fine forceps.…”
Section: Sperm Viability Assaysmentioning
confidence: 99%
“…Climate change is threatening biodiversity around the globe [1][2][3] , and one potential driver is through heatinduced reductions in fertility [4][5][6] . The impact of heat on fertility is far-reaching in the animal kingdom, affecting mammals [7][8][9][10][11] , birds 12 , fish 13 , nematodes 14 , and insects 4,[15][16][17][18][19][20][21] . At temperatures of 40-43 ͦ C, spermatogenesis is compromised 22 , sperm viability drops 4,18,19 , sperm are less competitive 4 , and motility is compromised 15,23,24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation